Establishment of a tamoxifen-inducible Cre-driver mouse strain for widespread and temporal genetic modification in adult mice - Ichise, Hirotake (Exp Anim, 2016)
Temporal genetic modification of mice using the ligand-inducible Cre/loxP system is an important technique that allows the bypass of embryonic lethal phenotypes and access to adult phenotypes. In this study, we generated a tamoxifen-inducible Cre-driver mouse strain for the purpose of widespread and temporal Cre recombination. The new line, named CM32, expresses the GFPneo-fusion gene in a wide variety of tissues before FLP recombination and tamoxifen-inducible Cre after FLP recombination. Using FLP-recombined CM32 mice (CM32Δ mice) and Cre reporter mouse lines, we evaluated the efficiency of Cre recombination with and without tamoxifen administration to adult mice, and found tamoxifen-dependent induction of Cre recombination in a variety of adult tissues. In addition, we demonstrated that conditional activation of an oncogene could be achieved in adults using CM32Δ mice. CM32Δ;T26 mice, which harbored a Cre recombination-driven, SV40 large T antigen-expressing transgene, were viable and fertile. No overt phenotype was found in the mice up to 3 months after birth. Although they displayed pineoblastomas (pinealoblastomas) and/or thymic enlargement due to background Cre recombination by 6 months after birth, they developed epidermal hyperplasia when administered tamoxifen. Collectively, our results suggest that the CM32Δ transgenic mouse line can be applied to the assessment of adult phenotypes in mice with loxP-flanked transgenes.